Production, partial purification, and characterization of a glucoamylase from Epicoccum nigrum - Martim, Damaris Batistão; Santos, Fabiane Cristina dos; Barbosa-Tessmann, Ione Parra (Acta Scientiarum. Biological Sciences, 2023)
Starch processing industries use amylases, accounting for approximately 30% of the world’s enzyme market. Previously, an amylase-producing strain of Epicoccum nigrum was isolated from maize grains. Although E. nigrum amylase production is already reported in the literature, no published data on production optimization or characterization of the produced enzyme exists. The objectives of this work were to improve the amylase production by the E. nigrum PG 16 strain and to purify and characterize the produced enzyme. The E. nigrum PG 16 amylase production best conditions in submerged culture were: inoculum of 4% (v v-1) of a five-days-old stationary culture homogenate, agitation at 100 rpm, 25°C, natural light, 72 hours of incubation, starch as the carbon source, and an initial medium pH of 7.0. A molecular exclusion chromatography profile has shown the production of only one amylase, which was partially purified with ammonium precipitation and dialysis. The enzyme optima pH and temperature are 6.0 and 50°C, respectively. The partially purified enzyme lost its activity when incubated for 30 min in temperatures above 40°C, presenting a T50 of 46.25°C. The KM and Vmax of the partially purified enzyme are 1.72 mg mL-1 of starch and 0.15 mg min-1 of degraded starch, respectively. The ion Ca2+ slightly activated the studied enzyme. The ions Cu2+, Zn2+, and Fe3+ and the detergents SDS and Tween 80 acted as inhibitors of the studied enzyme. The partially purified enzyme released glucose from p-nitrophenyl α-D-glucopyranoside (p-NPG). Glucose was the enzyme’s main product from starch hydrolysis, as evidenced by thin-layer chromatography. The E. nigrum PG 16 studied enzyme is a glucoamylase and represents an alternative for enzymatic starch hydrolysis.